Identifying syntactic patterns in Croatian WordNet synset definitions - Bekavac, Božo; Šojat, Krešimir (2010)
The paper presents syntactic pattern definitions designed for Croatian WordNet in order to create unambiguous and consistent synset definitions. The rules are implemented in form of finite-state transducers and tested on already existing version of Croatian WordNet. Results are presented using standard evaluation measures.
Projekt MZOS
ENG